Reframing the concept of alternative livelihoods. Issue 1 (2nd November 2015) - Wright, Juliet H.; Hill, Nicholas A. O.; Roe, Dilys; Rowcliffe, J. Marcus; Kümpel, Noëlle F.; Day, Mike; Booker, Francesca; Milner‐Gulland, E. J.
Abstract: Alternative livelihood project (ALP) is a widely used term for interventions that aim to reduce the prevalence of activities deemed to be environmentally damaging by substituting them with lower impact livelihood activities that provide at least equivalent benefits. ALPs are widely implemented in conservation, but in 2012, an International Union for Conservation of Nature resolution called for a critical review of such projects based on concern that their effectiveness was unproven. We focused on the conceptual design of ALPs by considering their underlying assumptions. We placed ALPs within a broad category of livelihood‐focused interventions to better understand their role in conservation and their intended impacts. We dissected 3 flawed assumptions about ALPs based on the notions of substitution, the homogenous community, and impact scalability. Interventions based on flawed assumptions about people's needs, aspirations, and the factors that influence livelihood choice are unlikely to achieve conservation objectives. We therefore recommend use of a sustainable livelihoods approach to understand the role and function of environmentally damaging behaviors within livelihood strategies; differentiate between households in a community that have the greatest environmental impact and those most vulnerable to resource access restrictions to improve intervention targeting; and learn more about the social–ecological system within which household livelihood strategies are embedded. Rather than using livelihood‐focused interventions as a direct behavior‐change tool, it may be more appropriate to focus on either enhancing the existing livelihood strategies of those most vulnerable to conservation‐imposed resource access restrictions or on use of livelihood‐focused interventions that establish a clear link to conservation as a means of building good community relations. However, we recommend that the term ALP be replaced by the broader term livelihood‐focused intervention. This avoids the implicit assumption that alternatives can fully substitute for natural resource‐based livelihood activities.